2022
DOI: 10.1007/s12350-021-02550-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of patient motion on quantitative accuracy in cardiac 15O-water positron emission tomography

Abstract: Background Patient motion is a common problem during cardiac PET. The purpose of the present study was to investigate to what extent motions influence the quantitative accuracy of cardiac 15O-water PET/CT and to develop a method for automated motion detection. Method Frequency and magnitude of motion was assessed visually using data from 50 clinical 15O-water PET/CT scans. Simulations of 4 types of motions with amplitude of 5 to 20 mm were performed based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…In this part of the study, we investigated the ability to visually detect and manually correct patient motion. Data consisted of myocardial stress 15 O-water PET scans with simulated motion from Nordström et al 6 Of the original 17 simulated motions, five motions with low amplitude were omitted, and instead, 4 new motions were added. Thus, this study included a data set consisting of 16 different simulated motions with an amplitude of 5 to 20 mm applied to data from 10 motion-free clinical scans, yielding 160 simulated scans.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this part of the study, we investigated the ability to visually detect and manually correct patient motion. Data consisted of myocardial stress 15 O-water PET scans with simulated motion from Nordström et al 6 Of the original 17 simulated motions, five motions with low amplitude were omitted, and instead, 4 new motions were added. Thus, this study included a data set consisting of 16 different simulated motions with an amplitude of 5 to 20 mm applied to data from 10 motion-free clinical scans, yielding 160 simulated scans.…”
Section: Methodsmentioning
confidence: 99%
“… 4 , 5 Previous studies on patient motion have reported a high occurrence of motion, with 30-68% of image acquisitions affected. 6 10 Motion can be random with independent patterns of motion magnitude and direction or due to coughing. 11 , 12 However, the most common causes of patient motion are related to discomfort from pharmacological stress agents, and the associated changes in respiratory pattern, which may result in a continuous displacement of the mean position of the heart, 13 or even rapid displacements which may appear like random motion.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations